Intensity threshold variation method in the post-irradiation analysis of Fluorescent Nuclear Track Detectors for neutron dosimetry - Becker, Anna; Jäkel, Oliver; Vedelago, José (Radiation physics and chemistry, 2022)
Fluorescent Nuclear Track Detectors (FNTDs) are biocompatible passive detectors and a promising tool for neutron dosimetry applications, such as in-phantom measurements within the scope of ion therapy. Sensitivity differences between individual detectors however complicate the post-irradiation analysis process, making detector comparability and consequently dose assessment challenging. Therefore, improvements in the analysis method are needed to account for the observed sensitivity effects. In this work, the FNTD technology was implemented for neutron dosimetry using a standard Am-241/Be neutron source for irradiation and a confocal laser scanning microscope for detector readout. Acquired images were evaluated in terms of the track number of recoil proton signals behind a polyethylene converter, which was found to be related to dose. This study presents a new methodology for the post-irradiation data analysis, based on the variation of the intensity threshold parameter during the proton track identification process. The procedure was tested within individual detectors in stepwise irradiation experiments, validating the consistency of the proposed methodology. The application of the method to an extended number of FNTDs was able to account for sensitivity impacts and enabled comparability between the different detectors. A calibration curve based on the observed linear relation between dose and the number of identify tracks was obtained, that can be used for future implementation of FNTDs in neutron dosimetry.